Peculiarity of currant and perpetual repair cell culture - Tynykulov, M.K. (Fundamental and Experimental Biology, 2022)
Perpetual raspberry is a group of raspberry varieties distinguished by their ability to bear fruit on two-year and one-year stem shoots. Black currant (Ríbes nígrum) is a deciduous shrub, family Gooseberry (Grossulari-aceae), related to currants (Ribes). The article presents methods of cell selection of perpetual raspberries and currants. Crop varieties resistant to extreme natural factors, obtaining high harvest, and two harvests per year were considered. The chemical composition of the used nutrient medium, the content of micro- and macro-elements, and organic substances were taken into account. The qualitative composition of callus shoots extracted from plant cells was determined. A strong relationship between the frequency of callusogenesis in black currant and the balance of phytohormones in the nutrient medium has been shown. Progress in the field of gene and cell biotechnology is directly related to the development of the basics of the cultivation of plant cells and tissues under in vitro conditions. In addition, it is of particular interest to choose a suitable nutrient medium, to establish the mode of cultivation in order to determine the species and volume of explants, the totipotency of representatives of different taxonomic groups of plants. At present, this unique ability of somatic cells is found in various cultures, most of which are annual and practically vegetative propagating plants. These are vegetable crops and ornamental plants, the list of which grows annually. The scientific novelty of the work is the possibility of obtaining somatic h ybrids and transgenic plants of repair raspberry and black currant using biotechnology methods. Therefore, the study of theoretical foundations and development of applied aspects of cells and tissues of perennial plants, in particular fruit and berry and agricultural crops, their accelerated reproduction, obtaining somatic hybrids and transgenic plants are considered relevant.